Development Of Hand Sanitizer and Introduction of Herbal Function as Inunodulator for Muhammadiyah/Aisyiyah Citizen in Sukabumi Regency - Reni Mulyani; Lela L Khumaisah (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
During the Covid-19 pandemic, people are required to comply with health protocols, including frequently washing hands with running water or using hand sanitizers to minimize contamination of the Covid-19 virus. To increase the body's resistance or immunity against the Covid-19 virus, people are also required to consume nutritious food. In this community service, training will be conducted for Muhammadiyah and Aisyiyah residents of Sukabumi Regency so that they can make their own hand sanitizer that is environmentally friendly and inexpensive. Muhammadiyah and Aisyiyah residents were also given knowledge about herbs or medicinal plants to increase body immunity against Covid-19. This community service was carried out for 4 months with partners from the Muhammadiyah City and Sukabumi Regency associations, and the Muhammadiyah women's autonomous organization, namely the Aisyiyah Regional Executive, Sukabumi Regency. Community service activities carried out by making WHO standard hand sanitizers and seminars on herbal plants that function as immunodulators